Outward-rectifying potassium channels GORK and SKOR function in regulation of root growth under salt stress in Arabidopsis thaliana - Hiya, Hafsa Jahan (Journal of plant physiology, 2024)
Copyright © 2024 The Authors. Published by Elsevier GmbH.. All rights reserved.